2020
DOI: 10.1177/0886260520978179
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Sexual Victimization and Health Outcomes Among LGBQA College Students: Examining the Moderating Role of Social Support

Abstract: Prior studies have demonstrated that sexual minority college students are two to four times more likely to experience sexual victimization (e.g., sexual assault and/or unwanted or uncomfortable sexual experiences) compared to their heterosexual counterparts. However, research that has focused on the detrimental effects of sexual victimization on health outcomes has paid more attention to heterosexual college samples and community-based adults. Understanding how sexual victimization influences mental health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Studies measuring victimisation as a distinct category, such as combining being teased or bullied, hit or beaten up, treated unfairly and public ridicule due to actual or perceived sexual minority status, had a range of 4% (Lowery et al., 2020 ) to 69% (Veale et al., 2017 ). Six studies examined sexual abuse (Atteberry et al., 2020 ; De Laney et al., 2020 ; Donahue et al., 2017 ; D’Augelli et al., 2006 ; Hatchel et al., 2018 ; Zhao et al., 2020 ). Nine percent (D’Augelli et al., 2006 ) to 48% (Hatchel et al., 2018 ) of LGBT+ youth samples reported sexual assault and unwanted or uncomfortable sexual experiences (e.g., rape, attempted rape or made to perform sexual acts).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies measuring victimisation as a distinct category, such as combining being teased or bullied, hit or beaten up, treated unfairly and public ridicule due to actual or perceived sexual minority status, had a range of 4% (Lowery et al., 2020 ) to 69% (Veale et al., 2017 ). Six studies examined sexual abuse (Atteberry et al., 2020 ; De Laney et al., 2020 ; Donahue et al., 2017 ; D’Augelli et al., 2006 ; Hatchel et al., 2018 ; Zhao et al., 2020 ). Nine percent (D’Augelli et al., 2006 ) to 48% (Hatchel et al., 2018 ) of LGBT+ youth samples reported sexual assault and unwanted or uncomfortable sexual experiences (e.g., rape, attempted rape or made to perform sexual acts).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported PTSD symptoms as a result of experiencing ACEs, where 9% (D’Augelli et al., 2006 ) to 33.9% (Duarte et al., 2018 ) met the criteria for a diagnosis. Sexual victimisation explained 23.3% of variance in PTSD disorder (DeLaney et al., 2020 ). Six studies looked at alcohol use, abuse or dependence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, nearly half (47%) of gender minority individuals experience sexual violence in their lifetimes. 5 , 6 Furthermore, studies 7 , 8 of gender minority college students found that these individuals had higher levels of SV trauma-related sequalae, including posttraumatic stress disorder, than their cisgender peers.…”
Section: Introductionmentioning
confidence: 99%